2014
DOI: 10.1007/s00221-014-4071-1
|View full text |Cite
|
Sign up to set email alerts
|

Internal models of upper limb prosthesis users when grasping and lifting a fragile object with their prosthetic limb

Abstract: Internal models allow unimpaired individuals to appropriately scale grip force when grasping and lifting familiar objects. In prosthesis users, the internal model must adapt to the characteristics of the prosthetic devices and reduced sensory feedback. We studied the internal models of 11 amputees and eight unimpaired controls when grasping and lifting a fragile object. When the object was modified from a rigid to fragile state, both subject groups adapted appropriately by significantly reducing grasp force on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 52 publications
1
32
1
Order By: Relevance
“…30,31 These findings were higher than our mean score of 13.7blocks/min in experienced upper limb amputees, probably because the previous studies were executed with the patient's own prosthesis instead of a simulator, used a body-powered simulator, or concerned a younger test population. A decrease in BBT scores related to age has been demonstrated previously.…”
Section: Discussioncontrasting
confidence: 79%
“…30,31 These findings were higher than our mean score of 13.7blocks/min in experienced upper limb amputees, probably because the previous studies were executed with the patient's own prosthesis instead of a simulator, used a body-powered simulator, or concerned a younger test population. A decrease in BBT scores related to age has been demonstrated previously.…”
Section: Discussioncontrasting
confidence: 79%
“…However, the current study also pointed out that this process has a time dimension and that the model will inevitably deteriorate if not updated again, even in the ideal conditions. The conclusion of another, very recent study (Lum et al 2014) was that the users of open-loop prostheses employ internal models for grasping, but that the accuracy of these models is poor. This is in accordance with what was observed here for the myoelectric control.…”
Section: The Role Of Feedbackmentioning
confidence: 97%
“…Recent studies demonstrated that prosthesis users, similar to able-bodied subjects, might employ internal models for feedforward control of prostheses with no somatosensory feedback (Lum et al 2014;Metzger et al 2010;Weeks et al 2000). However, there is only a single study (Saunders and Vijayakumar 2011) addressing the role of feedforward and feedback processes when using a closed-loop prosthesis.…”
Section: Introductionmentioning
confidence: 98%
“…The study of Lum et al shows that fragile object manipulation is inferior with a prosthesis than with the intact biological hand [24]. However, the performance of the VC BPP user was exceptional compared to the other prosthetic users.…”
Section: Discussionmentioning
confidence: 99%
“…In order to inherently include interaction force limits in this manipulation task, a “mechanical egg” [5] was used which offers repeatable limits: at too little force subjects can’t lift it, and at an adjustable level it “breaks” mechanically. Abstract collapsible objects have been used in diverse studies investigating feedback and pinch force control [5,24], since they offer a natural challenging dynamic grasping task. As prosthetic users aim to execute grasping tasks as quickly as they would with an intact hand, time to execute the task was taken as an outcome measure.…”
Section: Introductionmentioning
confidence: 99%